Analisis Pemeliharaan Pesawat Pasca Insiden Bird Strike pada Engine #1 - Yogi Prisma Caysar Pradewa; Aziz Faudzan Alam (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study aims to analyze the aircraft maintenance procedures following a bird strike incident on Engine #1, focusing on incident identification, maintenance actions taken, damage evaluation, follow-up recommendations, and compliance with aviation industry standards. Data for the study were obtained through official technical documentation such as the Technical Standard Manual (TSM) and Aircraft Maintenance Manual (AMM). Data analysis was conducted using the Miles & Huberman method, which includes stages of data collection, data reduction, data presentation, and conclusion drawing. Data validity was ensured through source triangulation, relying on various related documents to strengthen the findings. The results showed that the maintenance procedures applied were in accordance with international standards. Post-incident maintenance was carried out systematically and well-documented, with no procedural violations or technical neglect. The damage evaluation of Engine #1 revealed that the corrective actions implemented were effective, ensuring the aircraft's safe return to service. Recommendations for further maintenance include enhancing supervision of existing procedures. Overall, the post-incident maintenance met best practices in the civil aviation industry, ensuring aircraft safety and reliability.